Bi Catalyzed CdS Nanowires With Temperature-Dependent Morphologies for Potential Applications in Solar Cells - Zayas-Bazán, P. G.; Gutierrez Z-B, K.; de Melo, O.; Santana, G.; Sastré-Hernández, J.; Aguilar-Hernández, J. R.; Tufiño-Velázquez, M.; Contreras-Puente, G. (Frontiers in Materials, 2020)
In this work, we present the preparation of CdS nanowires (CdS-NWs) using the chemical vapor deposition technique and Bi nanoparticles as catalysts. The obtained nanowires were found to be in the hexagonal Greenockite structure according XRD diffractograms and Raman spectroscopy measurements. In dependence of the growth temperature, two kinds of morphologies were observed in SEM images. At low temperature, a high density and homogenous population of thin and straight nanowires grown through the Vapor-Liquid-Solid mechanism was observed. At higher temperature, thicker bunches of braided nanowires were observed. A quantitative analysis of the temperature-dependent photoluminescence spectra of the CdS-NWs was carried out.